2014
DOI: 10.1111/anu.12051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of algal species and concentration on development and fatty acid composition of two harpacticoid copepods,Tisbesp. andTachidius discipes, and a discussion about their suitability for marine fish larvae

Abstract: We compared the development and fatty acid content of the harpacticoid copepods Tachidius discipes and Tisbe sp. fed with different microalgal species (Dunaliella tertiolecta, Rhodomonas sp., Phaeodactylum tricornutum, Isochrysis galbana and a concentrate of Pavlova sp.), which differed in cell size and fatty acid composition. Tisbe could develop in 11 days with every alga to the same average stage, whereas Tachidius developed poorly when fed with Isochrysis and Dunaliella. Feeding with Phaeodactylum resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 59 publications
(93 reference statements)
2
37
0
Order By: Relevance
“…The highest densities of S. leucops were reached when their diet was supplemented with fresh algae but not detritus, probably because of the poor nutritional quality of the latter (Sterner and Hessen, 1994). Nutritional value of these resources is reflected in the somatic phosphorus content and composition of fatty acids (DeMott and Pape, 2005;Arndt and Sommer, 2014). Paramecium sp.…”
Section: Discussionmentioning
confidence: 99%
“…The highest densities of S. leucops were reached when their diet was supplemented with fresh algae but not detritus, probably because of the poor nutritional quality of the latter (Sterner and Hessen, 1994). Nutritional value of these resources is reflected in the somatic phosphorus content and composition of fatty acids (DeMott and Pape, 2005;Arndt and Sommer, 2014). Paramecium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of POC (particulate organic carbon) and PON (particulate organic nitrogen) were conducted as described in Sharp [52] by gas-chromatography in an organic elemental analyzer (Thermo Flash 2000; Thermo Fisher Scientific Inc., Schwerte, Germany). FAs were measured as fatty acid methyl esters (FAMEs) using a gas-chromatograph (Trace GC-Ultra; Thermo Fisher Scientific Inc.) according to the procedure detailed in Arndt and Sommer [53]. …”
Section: Methodsmentioning
confidence: 99%
“…Feng et al (2017a) suggested that the decreased calcification in E. huxleyi may be caused by the increased requirement of energy to counteract intracellular acidification. The increased activity of carbonic anhydrase (CA) at low pCO 2 may explain the lack of a significant effect of pCO 2 on the photosynthetic or growth rate (Feng et al, 2017a), as upregulation of CA at low DIC was previously observed (Bach et al, 2013).…”
Section: Responses Of Pic : Pocmentioning
confidence: 97%